BERTAHANNYA BANGSAWAN BONE DI TENGAH PERUBAHAN REZIM, 1811-1946 - Suryadi Mappangara (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2011)
The implementation of the autonomy Law in the early 2001 in Indonesia haslead to the emergence of petty kings in several regions. However, the diversityof the local political history will be in?uenced or in?uence the ways in whichregional autonomy are practiced by local elites. By taking the political historyof Bone from 1811 to 1946 as a case study, this dissertation shows that thecurrent petty kings have long been maintained by decendants of aristocraticelite in Bone. There are three interrelated factors that make the aristocratsin Bone are able to survive in maintaining their power until now; namelypolitical marriages, social networks, and patron-client relationship.The colonial government failed to understand three important factors embedded in the long political history of Bone. This lack of knowledge about history and political culture of Bone has led to ongoing con?ict between Bonesaristocrats and the colonial government. By using local sources,Lontara andcolonial sources, the dissertation attempts to provide balanced analysis of thedynamics of local political structures of Bone from the period 1811 to 1946.Keywords: history, aristocrats, social network, political marriages, patronclient relationship, Bone, South Sulawesi.